Money, Output, and Inflation: Evidence from Pakistan (The Pakistan Development Review, 2006)
Pakistan has experienced inflationary episodes in the last thirty years. “Why has inflation been high in some of the periods?” is a debatable question. There are at least three possible candidate answers to this question; monetary policy actions, supply side factors and/or inflation in the rest of the world (trading partner countries). To test whether monetary policy actions are responsible for episodes of high inflation is the objective of this study. Khan and Schimmelpfennig (2006) studied the relative importance of monetary factors and supply side factors for inflation and found that monetary factors had played dominant role in inflation determination. Agha, et al. (2005), while studying transmission mechanism in Pakistan, found that inflation and output respond significantly to shocks in monetary policy instrument. However both studies depend on small data set. In this study Near-VAR approach has been used to model inflation, real GDP gap and reserve money and then impulse response functions are estimated by imposing restrictions consistent with economic theory, [Enders (2004); Sims (1986)]. Our results show the standard hump shaped response of output and inflation to monetary policy shock, reaching at peak after several quarters. Next Granger causality test is applied to test the direction of causality between inflation and reserve money and real GDP gap and reserve money. It is seen that inflation is Granger caused by reserve money but not the other way around. This result does not hold in case of reserve money and real GDP gap.